Adaptive Financial Controlling in Times of Crisis: Evidence from Eastern European Retail (Global Journal of Management and Business Research, 2025)
Abstract not found
Keywords: Key Account Manager; Beko Europe (formerly Whirlpool Ukraine) Kyiv; Ukraine; Member